2017
DOI: 10.1038/cddis.2017.452
|View full text |Cite
|
Sign up to set email alerts
|

Curcumin reversed chronic tobacco smoke exposure induced urocystic EMT and acquisition of cancer stem cells properties via Wnt/β-catenin

Abstract: Tobacco smoke (TS) is the most important single risk factor for bladder cancer. Epithelial–mesenchymal transition (EMT) is a transdifferentiation process, involved in the initiation of TS-related cancer. Cancer stem cells (CSCs) have an essential role in the progression of many tumors including TS-related cancer. However, the molecular mechanisms of TS exposure induced urocystic EMT and acquisition of CSCs properties remains undefined. Wnt/β-catenin pathway is critical for EMT and the maintenance of CSCs. The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
59
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 69 publications
(61 citation statements)
references
References 46 publications
2
59
0
Order By: Relevance
“…PKCζ affects β‐catenin stability, further affecting stem cell function . The Wnt/β‐catenin pathway plays an important role in tumor cell EMT and stemness; such report is consistent with our results from KEGG pathway analysis based on the differential genes between cPLA2α KD and KD/SCR CSCs and from mass spectrometry analysis. Many β‐catenin molecules bound to the cytomembrane with E‐cadherin, and less nuclear translocation of β‐catenin occurred when PKCζ was knocked down regulated by cPLA2α inhibition, leading to increased E‐cadherin‐mediated cell‐to‐cell adhesion and blockage of EMT and metastasis.…”
Section: Discussionsupporting
confidence: 91%
“…PKCζ affects β‐catenin stability, further affecting stem cell function . The Wnt/β‐catenin pathway plays an important role in tumor cell EMT and stemness; such report is consistent with our results from KEGG pathway analysis based on the differential genes between cPLA2α KD and KD/SCR CSCs and from mass spectrometry analysis. Many β‐catenin molecules bound to the cytomembrane with E‐cadherin, and less nuclear translocation of β‐catenin occurred when PKCζ was knocked down regulated by cPLA2α inhibition, leading to increased E‐cadherin‐mediated cell‐to‐cell adhesion and blockage of EMT and metastasis.…”
Section: Discussionsupporting
confidence: 91%
“…Numerous studies have suggested the importance of Wnt-b-catenin signaling in several cancers (44). Furthermore, Wnt-b-catenin has been shown to play important roles during epithelial-mesenchymal transition (45), cell proliferation and metastasis (24), and drag resistance (46) in bladder cancer. In the present study, RBM5 knockdown activated the Wnt-b-catenin pathway by promoting the expression of b-catenin and cyclin D1 while decreasing the apoptosis marker caspase-3 at the protein level.…”
Section: Discussionmentioning
confidence: 99%
“…Cigarette exposure not only increases cell malignancy but also increases the expression of cancer stem cells, which make cancer cells more prone to metastasis and recurrence. 4,24 Studies have shown that cigarettes promote the initiation, development, and metastasis of bladder cancer. 19,21,25 Clinical studies have found that compared with non-smokers, smokers with bladder cancer have significantly increased cancer recurrence rates and a reduced non-tumor survival period, which may be related to cigarette-induced EMT in bladder cancer cells and promoted cancer stem cells.…”
Section: Discussionmentioning
confidence: 99%
“…3 Although the etiology of bladder cancer has not been elucidated, a large number of epidemiological studies abroad have confirmed that cigarette smoke (CS) increases the incidence of bladder cancer, with the risk for smokers increasing approximately twofold to sixfold from that of nonsmokers. 4,5 It is commonly reported that the incidence of bladder cancer in men is much higher than that in women, which is strongly associated with CS. 6 There are more than 60 established carcinogens, which have been classified into five major groups: polycyclic aromatic hydrocarbons (PAH), nicotine-derived nitrosamines, azaarenes, miscellaneous organic compounds, and inorganic compounds.…”
Section: Introductionmentioning
confidence: 99%